2014
DOI: 10.1016/j.ydbio.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Annexin A4 as a hepatopancreas factor involved in liver cell survival

Abstract: To gain insight into liver and pancreas development, we investigated the target of 2F11, a monoclonal antibody of unknown antigen, widely used in zebrafish studies for labeling hepatopancreatic ducts. Utilizing mass spectrometry and in vivo assays, we determined the molecular target of 2F11 to be Annexin A4 (Anxa4), a calcium binding protein. We further found that in both zebrafish and mouse endoderm, Anxa4 is broadly expressed in the developing liver and pancreas, and later becomes more restricted to the hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 69 publications
4
39
0
Order By: Relevance
“…High resolution melt curve analysis (HRMA) and sequencing of the sox4a and sox4b target regions in individual injected embryos confirmed that short indels were generated in the sox4 gRNA/Cas9 injected individuals with high efficiency (Figure S1P-Q and data not shown), with the mutation frequency ranging from 52.78% to 94.44%. These data suggest that the CRISPRs induced bi-allelic gene inactivation in mosaic injected embryos, as has been reported previously in zebrafish and mice (Jao et al, 2013; Yen et al, 2014; Zhang et al, 2014), resulting in ocular phenotypes similar to those seen in the sox4 morphants. Taken together, these results strongly support the specificity of the sox4 morphant coloboma phenotype.…”
Section: Resultssupporting
confidence: 86%
“…High resolution melt curve analysis (HRMA) and sequencing of the sox4a and sox4b target regions in individual injected embryos confirmed that short indels were generated in the sox4 gRNA/Cas9 injected individuals with high efficiency (Figure S1P-Q and data not shown), with the mutation frequency ranging from 52.78% to 94.44%. These data suggest that the CRISPRs induced bi-allelic gene inactivation in mosaic injected embryos, as has been reported previously in zebrafish and mice (Jao et al, 2013; Yen et al, 2014; Zhang et al, 2014), resulting in ocular phenotypes similar to those seen in the sox4 morphants. Taken together, these results strongly support the specificity of the sox4 morphant coloboma phenotype.…”
Section: Resultssupporting
confidence: 86%
“…The limitation of this method is that rare Tg(Tp1-MmHbb:EGFP) um14 -negative terminal cells will be excluded from this computational assay. The Anxa4 antibody (mAb 2F11) recognizes most of the biliary epithelial cells (Sakaguchi et al, 2008;Zhang et al, 2014), and this algorithm can also analyze the Anxa4 expression pattern (Fig. S6).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sorting nexon 7 (snx7) and annexin A4 (anxa4) are both required for hepatoblast survival[40,41]. Similarly, the small nuclear RNA (snRNA) transcription complex component snap4c is required for BEC survival[42].…”
Section: Introductionmentioning
confidence: 99%